Financial Performance of the Pharmaceutical Industry In Indonesia - Murti, Wahyu; Kurniati, Arni; Isman, Isman (Dinasti International Journal of Digital Business Management, 2023)
The financial performance of the pharmaceutical sector globally can be seen in the pharmaceutical sector in each country's capital market. Important information in the financial performance of the information sector is the financial statements provided by each pharmaceutical company that goes public. using secondary data with panel data analysis methods. The results showed that Return on Equity (ROE) partially had a significant positive effect on Price to Book Value (PBV) in pharmaceutical subsector companies listed on the IDX in 2013-2021.Currently Ratio (CR) partially has a significant negative effect on Price to Book Value (PBV) in pharmaceutical subsector companies listed on the IDX in 2013-2021. Debt to Equity Ratio (DER) partially has a significant positive effect on Price to Book Value (PBV) in pharmaceutical subsector companies listed on the IDX in 2013-2021. The results of the F test show that Return on Equity (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER) together have a significant influence on Price to Book Value (PBV) in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. IDX in 2013-2021 of 0.858833 which means that PBV is influenced by ROE, CR and DER by 87.93%, the remaining 12.07% is influenced by factors other than the factors above. checked. Novelty in Return On Equity research which has the greatest influence on Book value